A selection method of municipal solid waste reduction in East Lombok, West Nusa Tenggara Province. Issue 1 (November 2021) - Septarini, S; Huboyo, H S; Sudarno,
Abstract: Waste management is an important activity in human life that aims to find solutions to the waste problem. The province and local governments in Indonesia are responsible for waste management. The volume of municipal solid waste (MSW) in West Nusa Tenggara province, specifically in East Lombok, reached 2.792 m 3 /day. The public area for waste processing is technically limited. In East Lombok, there are 58 Transfer Post (TPS) units, although the majority are not operational. In East Lombok, the majority of the population (86.9%) did not separate their MSW. The volume of MSW in East Lombok, particularly MSW from urban areas, is affected by population expansion; therefore, the purpose of this paper is to investigate the best scenarios for implementation in the East Lombok district using four approaches: waste reduction through recycling, composting, incinerating and pyrolisis in the TPS. According to the modelling, scenarios 2 and 3 have the same impact on waste reduction. The percentage of total waste reduction can be seen. It has the potential to reduce complete waste by up to 50%. It applies to the method in East Lombok.